Taxpayers compliance behaviour: economic factors approach - Mohd Rizal Palil; Mohamad Abdul Hamid; Mohd Hizam Hanafiah (Penerbit Universiti Kebangsaan Malaysia, 2013)
Many developing countries have been integrating multiple tax brackets within the reforms of their respective tax regimes. Since tax systems were introduced in Asian countries several centuries ago, the determinants of tax compliance have been found to differ between countries. No universal findings are highlighted by researchers pertaining to genuine tax compliance determinants among countries sharing similar tax systems, cultures and ethnicities. The present paper attempts to reveal the determinants of tax compliance in Malaysia in a self-assessment system (SAS) with special emphasis on individual taxpayers. Four tax compliance determinants are examined: the probability of being audited; the perception of government spending; tax rates; and the role of the tax authority. From a survey of 1,073 respondents, the results show that all four determinants have a significant impact on tax compliance. The results of the present study may be useful for policymakers in relation to improving tax compliance in light of the four factors. By identifying the a fore mentioned determining factors, the present study further contributes by providing evidence of other key tax compliance determinants in a developing country, particularly in Asia, that is generally under researched. These determinants are expected to affect tax compliance behaviour in other countries that have similar taxpayer backgrounds, cultures,economic environments and policies. The present study may also be utilised to provide further information to assist tax authorities in other Asian countries to improve their respective SAS plans in the future.